Electrospun PCL/PLA Scaffolds Are More Suitable Carriers of Placental Mesenchymal Stromal Cells Than Collagen/Elastin Scaffolds and Prevent Wound Contraction in a Mouse Model of Wound Healing - Vonbrunn, Eva; Mueller, Marc; Pichlsberger, Melanie; Sundl, Monika; Helmer, Alexander; Wallner, Stefanie Angela; Rinner, Beate; Tuca, Alexandru-Cristian; Kamolz, Lars-Peter; Brislinger, Dagmar; Glasmacher, Birgit; Lang-Olip, Ingrid (Frontiers in Bioengineering and Biotechnology, 2020)
Mesenchymal stem/stromal cells (MSCs) exert beneficial effects during wound healing, and cell-seeded scaffolds are a promising method of application. Here, we compared the suitability of a clinically used collagen/elastin scaffold (Matriderm) with an electrospun Poly(ε-caprolactone)/poly(l-lactide) (PCL/PLA) scaffold as carriers for human amnion-derived MSCs (hAMSCs). We created an epidermal-like PCL/PLA scaffold and evaluated its microstructural, mechanical, and functional properties. Sequential spinning of different PCL/PLA concentrations resulted in a wide-meshed layer designed for cell-seeding and a dense-meshed layer for apical protection. The Matriderm and PCL/PLA scaffolds then were seeded with hAMSCs, with or without Matrigel coating. The quantity and quality of the adherent cells were evaluated in vitro. The results showed that hAMSCs adhered to and infiltrated both scaffold types but on day 3, more cells were observed on PCL/PLA than on Matriderm. Apoptosis and proliferation rates were similar for all carriers except the coated Matriderm, where apoptotic cells were significantly enhanced. On day 8, the number of cells decreased on all carrier types except the coated Matriderm, which had consistently low cell numbers. Uncoated Matriderm had the highest percentage of proliferative cells and lowest apoptosis rate of all carrier types. Each carrier also was topically applied to skin wound sites in a mouse model and analyzed in vivo over 14 days via optical imaging and histological methods, which showed detectable hAMSCs on all carrier types on day 8. On day 14, all wounds exhibited newly formed epidermis, and all carriers were well integrated into the underlying dermis and showing signs of degradation. However, only wounds treated with uncoated PCL/PLA maintained a round appearance with minimal contraction. Overall, the results support a 3-day in vitro culture of scaffolds with hAMSCs before wound application. The PCL/PLA scaffold showed higher cell adherence than Matriderm, and the effect of the Matrigel coating was negligible, as all carrier types maintained sufficient numbers of transplanted cells in the wound area. The anti-contractive effects of the PCL/PLA scaffold offer potential new therapeutic approaches to wound care.